Pause & ponder : reflecting on your work with children - Meek, Kate; O'Sullivan, Annie ([Kiama, New South Wales] : Early Years Education Specialists, 2021)
Annotation. The purpose of this journal is to support Educators to think deeply about their practices by engaging in reflection as they care and educate children, to ensure that the decisions being made relate to the characteristics of their unique learning communities. The information provided is not 'the answer'. It is drawn from many sources, including our own personal experiences within the sector; through our relationships with many practitioners; some 'critical friends' who challenged us both as individuals and as Early Years Education Specialists (EYES); and our curiosity and ponderings around the research we have engaged with. Each of offering provides opportunities and tools to pause and ponder (and sometimes provoke) dialogue around the issues and complexities that may arise in the work you do with children, families, communities and your colleagues within your specific service context.
Keywords: Early childhood education; Early childhood educators; Australian